The perceived value and perceived benefits experienced by customers using travel agents - Nic S. Terblanche; Aimee Taljaard (South African Journal of Business Management, 2018)
Although many predictions have been made about the demise of travel agents because of the impact of the Internet on travel agencies, many customers still prefer that a travel agent should take care of their travel arrangements instead of doing it themselves. This study endeavours to identify the benefits customers perceive to obtain when they use a travel agent for their travel arrangements. The exploratory and confirmatory factor analyses following the personal in-depth interviews with 26 customers of a travel agency and an extensive literature review revealed significant positive relationships between four perceived benefits and customer loyalty. These perceived benefits were identified as financial benefits, emotional benefits, expertise and support. An assessment of the internal consistency of all these dimensions was undertaken and all the Cronbach's alpha coefficients of the dimensions were above the generally accepted cut-off value of 0.7. The structural model's fit statistics (X2 = 349.27; df = 125; X2/df = 2.79; RMSEA = 0.0548) suggested that the data fitted the theoretical model reasonably well.
Keywords: 650